Master batch, method for producing master batch, rubber composition for tires, method for producing rubber composition for tires, rubber material for tires, and tire

By using hydrophilic vapor phase silica and silane coupling agent in the rubber material for tires and mixing at low rotation speeds, the problem that the rubber material for tires in the prior art is difficult to balance wear resistance, low oil consumption and wet grip, and better tire performance is achieved.

CN119894965APending Publication Date: 2025-04-25TOKUYAMA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380067245.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-30
Filing Date
2023-10-11
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing rubber materials for tires are difficult to balance wear resistance, low oil consumption and wet grip, especially when wet silicon dioxide is used as a filler, the reduction in the amount of carbon black mixing leads to a reduction in wear resistance.

Method used

By using hydrophilic vapor phase silica as a filler and combining silane coupling agent in the masterbatch, kneading is performed at low speed by using a kneader to ensure sufficient dispersion of hydrophilic vapor phase silica and satisfying the specific M100, TB and EB relationships.

Benefits of technology

It achieves a balance of wear resistance, low fuel consumption and wet grip, improves the overall performance of rubber materials for tires, and is suitable for manufacturing high-performance tires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894965A_ABST
    Figure CN119894965A_ABST
Patent Text Reader

Abstract

Provided are: a rubber material for tires, which has an excellent balance among wear resistance, low fuel consumption, and wet grip; a master batch and a rubber composition for tires, which are suitable for the production of the rubber material for tires; a method for producing the master batch and the rubber composition for tires; and a tire comprising a tire member formed from the rubber material for tires. A rubber material for tires, which contains 5-90 parts by mass (inclusive) of a hydrophilic fumed silica and 1.5-30 parts by mass (inclusive) of a silane coupling agent per 100 parts by mass of a total rubber component comprising at least one selected from the group consisting of natural rubbers and synthetic rubbers, in the rubber material for tires, the stress at 100% elongation (M100: MPa), the tensile breaking strength (TB: MPa), and the tensile breaking elongation (EB:%) of the rubber material for tires satisfy the following relationship. TB * EB / M100 is greater than or equal to 4000 and less than or equal to
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a masterbatch, a method for producing the masterbatch, a rubber composition for a tire, a method for producing the rubber composition for a tire, a rubber material for a tire, and a tire. Specifically, it relates to a tire having excellent wear resistance and wet grip and low rolling resistance, and a material suitable for producing the tire. Background Art

[0002] In recent years, with the increasing attention paid to automobile safety, the requirements for low fuel consumption and driving stability have increased. In order to cope with this, a tire performance is required that also satisfies low heat generation with reduced rolling resistance, driving stability on wet and dry roads, and high wear resistance. In addition, improvements in reinforcing fillers and rubber components are being made to meet such requirements.

[0003] In the past, carbon black was used as a filler for rubber reinforcement. This is because carbon black can impart high wear resistance to tire rubber materials. However, by using carbon black alone, it is difficult to obtain a tire rubber material that achieves a high level of balance in wet grip, wear resistance and low fuel consumption. In response to such problems, wet silica is being mixed to replace carbon black. However, it is known that when wet silica is used as a filler, the amount of carbon black mixed is relatively reduced, so the reduction in the breaking strength and wear resistance of the tire rubber material is inevitable. In addition, there are the following problems: wet silica has poor dispersibility in rubber, the Mooney viscosity of the tire rubber material during mixing will increase, and the processability achieved by extrusion molding is poor.

[0004] Patent Documents 1 and 2 propose a tire rubber material comprising a rubber component, carbon black as a filler, wet silica, and an inorganic compound powder in order to obtain a tire rubber material having excellent fuel efficiency and wet grip without reducing wear resistance.

[0005] However, in order to fully obtain the improvement effect of wet grip and low fuel consumption, the tire rubber materials described in Patent Documents 1 and 2 need to be mixed with a large amount of inorganic compound powder, in which case there is a tendency that the wear resistance is easily reduced. Therefore, a tire rubber material with a better balance of wear resistance, low fuel consumption and wet grip has not yet been obtained.

[0006] In addition, Patent Document 3 proposes a tire rubber material that improves wear resistance and wet grip by using a specific carbon black together with a diene rubber component and wet silica, wherein the specific carbon black specifies properties such as DBP and N2SA calculated by two-dimensional projection image analysis of the polymer. However, the wear resistance, wet grip, and low fuel consumption are not fully satisfied.

[0007] Furthermore, Patent Document 4 proposes a vulcanized rubber composition, wherein the stress at 300% elongation (M300), the stress at 100% elongation (M100), the tensile strength at break (TB) and the tensile elongation at break (EB) of the vulcanized rubber composition have a prescribed relationship. It is described that the vulcanized rubber composition has excellent wear resistance. However, the wet grip is insufficient, and no evaluation is made on low fuel consumption.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2005-213353

[0011] Patent Document 2: Japanese Patent Application Publication No. 2018-150420

[0012] Patent Document 3: Japanese Patent Application Publication No. 2012-158661

[0013] Patent Document 4: International Publication No. 2018 / 128141 Summary of the invention

[0014] Problems to be solved by the invention

[0015] With increasing attention paid to automobile safety in recent years, automobile tires have been required to have not only high wear resistance and low fuel consumption but also excellent wet grip performance.

[0016] However, for the rubber materials for tires described in Patent Documents 1 to 4, in order to fully obtain the improvement effect of wet grip and low fuel consumption, it is necessary to mix more inorganic compound powders. In this case, there is a tendency for wear resistance to decrease. Therefore, a rubber material for tire with a better balance of wear resistance, low fuel consumption and wet grip has not yet been obtained.

[0017] The present invention has been completed in view of such actual conditions, and its purpose is to provide a rubber material for a tire having a better balance among wear resistance, low fuel consumption and wet grip, a masterbatch and a rubber composition for a tire suitable for the manufacture of the rubber material for a tire, a method for manufacturing the masterbatch and the rubber composition for a tire, and a tire including a tire component formed from the rubber material for a tire.

[0018] Solutions for solving problems

[0019] The present inventors have found that a tire rubber material having a better balance among wear resistance, fuel economy and wet grip can be obtained by blending hydrophilic fumed silica as a filler in a tire rubber composition and making M100, TB and EB satisfy a predetermined relationship.

[0020] However, since the volume of hydrophilic fumed silica is larger than that of wet silica, it has been found that the hydrophilic fumed silica is easily scattered during kneading in a Banbury mixer generally used for kneading rubber compositions, making it difficult to obtain a rubber composition in which the hydrophilic fumed silica is sufficiently dispersed.

[0021] Based on this finding, the present inventors have conducted further intensive studies and found that the above finding can be solved by using a kneading machine having a low rotor rotation speed, which is not generally used for kneading a rubber composition due to productivity problems.

[0022] As described above, the aspects of the present invention are as follows.

[0023] [1] A masterbatch comprising 13 parts by mass or more and 130 parts by mass or less of hydrophilic fumed silica and 1 part by mass or more and 40 parts by mass or less of a silane coupling agent, based on 100 parts by mass of a rubber component that is at least one selected from the group consisting of natural rubber and synthetic rubber.

[0024] [2] The masterbatch according to [1], wherein the BET specific surface area of ​​the hydrophilic fumed silica is 50 m 2 / g and above and 500m 2 / g or less.

[0025] [3] The masterbatch according to [1] or [2], comprising 1 part by mass or more and 40 parts by mass or less of a lubricant per 100 parts by mass of the rubber component.

[0026] [4] A method for producing a masterbatch, comprising: kneading a rubber component, hydrophilic fumed silica, and a silane coupling agent using a kneader.

[0027] [5] The method for producing a masterbatch according to [4], wherein the BET specific surface area of ​​the hydrophilic fumed silica is 50 m 2 / g and above and 500m 2 / g or less.

[0028] [6] The method for producing a masterbatch according to [4] or [5], further comprising kneading a lubricant.

[0029] [7] A rubber composition for a tire, comprising 5 parts by mass or more and 90 parts by mass or less of hydrophilic fumed silica and 1.5 parts by mass or more and 30 parts by mass or less of a silane coupling agent, based on 100 parts by mass of a total rubber component consisting of at least one selected from the group consisting of natural rubber and synthetic rubber.

[0030] [8] The rubber composition for a tire according to [7], wherein the rubber composition for a tire contains more than 0 parts by mass and 90 parts by mass or less of wet silica per 100 parts by mass of the total rubber component.

[0031] [9] The tire rubber composition according to [7] or [8], wherein the hydrophilic fumed silica has a BET specific surface area of ​​50 m 2 / g and above and 500m 2 / g or less.

[0032]

[10] The tire rubber composition according to [8] or [9], wherein the BET specific surface area of ​​the wet silica is 40 m 2 / g and above 220m 2 / g or less.

[0033]

[11] The rubber composition for a tire according to any one of [7] to

[10] , comprising the masterbatch according to any one of [1] to [3].

[0034]

[12] A method for producing a rubber composition for a tire, comprising: a step of kneading the masterbatch according to any one of [1] to [3] and at least one selected from the group consisting of natural rubber and synthetic rubber.

[0035]

[13] A rubber material for a tire, comprising 5 parts by mass or more and 90 parts by mass or less of hydrophilic fumed silica and 1.5 parts by mass or more and 30 parts by mass or less of a silane coupling agent, relative to 100 parts by mass of a total rubber component consisting of at least one selected from the group consisting of natural rubber and synthetic rubber, wherein the stress at 100% elongation (M100: MPa), tensile strength at break (TB: MPa) and tensile elongation at break (EB: %) of the rubber material for a tire satisfy the following relationship.

[0036] 4000≤TB×EB / M100≤13000.

[0037]

[14] The rubber material for a tire according to

[13] , wherein the rubber material for a tire contains more than 0 parts by mass and 90 parts by mass or less of wet silica per 100 parts by mass of the total rubber component.

[0038]

[15] The tire rubber material according to

[13] or

[14] , wherein the BET specific surface area of ​​the hydrophilic fumed silica is 50 m 2 / g and above and 500m 2 / g or less.

[0039]

[16] The tire rubber material according to

[14] or

[15] , wherein the BET specific surface area of ​​the wet silica is 40 m 2 / g and above 220m 2 / g or less.

[0040]

[17] A tire comprising: a tire component formed from the tire rubber material according to any one of

[13] to

[16] .

[0041] Effects of the Invention

[0042] According to the present invention, there can be provided a rubber material for a tire having a better balance among wear resistance, fuel economy and wet grip, a masterbatch and a rubber composition for a tire suitable for producing the rubber material for a tire, a method for producing the masterbatch and the rubber composition for a tire, and a tire including a tire component formed from the rubber material for a tire. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a process diagram of a method for producing a masterbatch according to the present embodiment.

[0044] Figure 2 This is a process diagram of a method for producing a rubber material for a tire using the masterbatch of the present embodiment. DETAILED DESCRIPTION

[0045] Hereinafter, the present invention will be described in detail based on specific embodiments in the following order.

[0046] 1. Masterbatch

[0047] 1.1. Rubber ingredients

[0048] 1.2. Hydrophilic fumed silica

[0049] 1.3. Silane coupling agent

[0050] 1.4. Other ingredients

[0051] 2. Masterbatch manufacturing method

[0052] 2.1. Kneader

[0053] 2.2. Mixing process

[0054] 3. Rubber composition for tires

[0055] 4. Method for producing tire rubber composition

[0056] 5. Rubber materials for tires

[0057] 6. Tires

[0058] (1. Masterbatch)

[0059] The masterbatch of the present embodiment is a kneaded product used to obtain a rubber material, and contains a rubber component, hydrophilic fumed silica, and a silane coupling agent.

[0060] The masterbatch of the present embodiment is a kneaded product to be kneaded with other compounding components including at least a rubber component. That is, the masterbatch of the present embodiment is kneaded with other compounding components including at least a rubber component to form a rubber composition for a tire.

[0061] In addition, in the masterbatch of the present embodiment, the content ratio of the hydrophilic fumed silica to the rubber component is higher than the content ratio of the hydrophilic fumed silica to the total rubber component contained in the tire rubber composition. That is, in the masterbatch of the present embodiment, the concentration of the hydrophilic fumed silica to the amount of the rubber component is higher than the concentration of the hydrophilic fumed silica to the amount of the rubber component in the tire rubber composition. In other words, the masterbatch of the present embodiment is a kneaded product containing hydrophilic fumed silica at a high concentration.

[0062] (1.1. Rubber component)

[0063] The rubber component contained in the masterbatch of the present embodiment is at least one selected from the group consisting of natural rubber and synthetic rubber. That is, the rubber component contained in the masterbatch may be only natural rubber or only synthetic rubber, or both natural rubber and synthetic rubber.

[0064] When the rubber component contained in the masterbatch is both natural rubber and synthetic rubber, the types and contents of the natural rubber and the synthetic rubber may be set according to the application of the rubber material for a tire, etc.

[0065] As natural rubber, modified natural rubbers such as natural rubber (NR), epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), deproteinized natural rubber (DPNR), and high-purity natural rubber (HPNR) can be listed. These natural rubbers can be used alone or in combination of two or more. In the present embodiment, NR is preferred as the natural rubber.

[0066] The NR is not particularly limited, and general NRs conventionally used in the rubber industry, such as SIR20, RSS3, and TSR20, can be used.

[0067] For example, when the masterbatch contains natural rubber and synthetic rubber, the content of NR in the rubber component (100 parts by mass) contained in the masterbatch is preferably 30 parts by mass or more, and more preferably 40 parts by mass or more, from the perspective of improving wear resistance. In addition, from the perspective of achieving a balance in tire properties that is a feature of the present invention, the content of NR is preferably 80 parts by mass or less, and more preferably 75 parts by mass or less.

[0068] As synthetic rubber, isoprene rubber (IR), butadiene rubber (BR), styrene butadiene rubber (SBR), styrene isoprene butadiene rubber (SIBR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), nitrile rubber (NBR) etc. can be used. These synthetic rubbers can be used alone or in combination of two or more. In the present embodiment, as synthetic rubber, SBR and BR are preferred.

[0069] The SBR is not particularly limited, and examples thereof include unmodified solution-polymerized SBR (S-SBR), unmodified emulsion-polymerized SBR (E-SBR), and modified SBRs thereof (modified S-SBR, modified E-SBR).

[0070] For example, when the masterbatch includes natural rubber and synthetic rubber, the content of SBR in the rubber component (100 parts by mass) contained in the masterbatch is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, for the reason of excellent processability during extrusion. In addition, the content of SBR is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, for the reason of suppressing heat generation inside the tire.

[0071] BR is not particularly limited, and for example, BR containing syndiotactic polybutadiene crystals can be used. As products containing syndiotactic polybutadiene crystals, examples thereof include BR1220 manufactured by Zeon (KK), high cis BRs such as BR130B and BR150B manufactured by Ube Industries (KK), and VCR412 and VCR617 manufactured by Ube Industries (KK).

[0072] For example, when the masterbatch contains natural rubber and synthetic rubber, the content of BR in the rubber component (100 parts by mass) contained in the masterbatch is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, for the reason of improving wear resistance. In addition, the content of BR is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, for the reason of suppressing heat generation inside the tire.

[0073] (1.2. Hydrophilic fumed silica)

[0074] Fumed silica is a micro-particle of silicon dioxide produced by hydrolyzing silicon tetrachloride at high temperature in a hydrogen-oxygen flame. Therefore, the production method of fumed silica is different from that of wet silica. Compared with wet silica, the primary particle size of the primary aggregate (smallest constituent) of fumed silica is smaller and the nitrogen adsorption BET specific surface area is larger. The particles of fumed silica aggregate and fuse into a rosary shape to form a large aggregate.

[0075] Fumed silica is divided into hydrophilic fumed silica and hydrophobic fumed silica based on the property for water. There are silanol groups on the surface of fumed silica. The silanol groups are chemically active, particularly easily react with water. Therefore, sometimes a surface treatment (hydrophobic treatment) is carried out by making the silanol groups react with other substances to reduce the reactivity with water. The fumed silica treated with hydrophobicity is called hydrophobic fumed silica, and the fumed silica not treated with hydrophobicity is called hydrophilic fumed silica.

[0076] In the present embodiment, hydrophobic fumed silica is distinguished from hydrophilic fumed silica by the modified hydrophobicity (M value) shown below. The modified hydrophobicity (M value) is a value obtained by a determination method using hydrophobic fumed silica floating in water but completely suspended in methanol. The method for determining the M value can adopt the method described in the embodiment of International Publication No. 2004 / 099075. When the M value is used to represent hydrophobic fumed silica and hydrophilic fumed silica, the M value of the hydrophobic fumed silica is greater than 1, and the M value of the hydrophilic fumed silica is less than 1.

[0077] The fumed silica contained in the masterbatch of the present embodiment is hydrophilic fumed silica. It is believed that hydrophilic fumed silica is more likely to form a structure caused by fumed silica than hydrophobic fumed silica, and this point will be described later. It is believed that by making such a structure exist in the rubber material for tire obtained by vulcanizing the rubber composition for tire, the wear resistance of the rubber material for tire is improved. On the other hand, in hydrophobic fumed silica, such a structure is less, and there is a tendency that the improvement of wear resistance is insufficient.

[0078] In this embodiment, even if the hydrophilic fumed silica is in a bulky state, the hydrophilic fumed silica is fully dispersed in the masterbatch by adopting the mixing method described later. Therefore, the tap density of the hydrophilic fumed silica is preferably less than 200 g / L, more preferably 150 g / L or less, and further preferably 100 g / L or less.

[0079] It should be noted that, in the present embodiment, the tap density of the hydrophilic fumed silica may be 200 g / L or more, but generally, when the tap density of the hydrophilic fumed silica is set to 200 g / L or more, a compression process is required, which requires an additional process and increases costs.

[0080] In addition, the lower limit of the tap density of the hydrophilic fumed silica is not particularly limited, but from the viewpoint of production, the lower limit of the tap density is, for example, 30 g / L.

[0081] In addition, in this embodiment, the BET specific surface area of ​​the hydrophilic fumed silica is preferably 50 m 2 / g or more, 80m 2 / g or more, 120m 2 / g or more, 200m 2 / g or more, 250m 2 / g or more, 300m 2 / g or more, 350m 2 By making the BET specific surface area of ​​the fumed silica within the above range, the number of silanol groups that become reaction points with the rubber component or the silane coupling agent in the hydrophilic fumed silica can be fully ensured. As a result, the hydrophilic fumed silica and the rubber component can be well mixed.

[0082] The upper limit of the BET specific surface area of ​​the hydrophilic fumed silica is not particularly limited, but is, for example, 500 m 2 / g. When the BET specific surface area of ​​the hydrophilic fumed silica is too small, the flame temperature during the production of the fumed silica needs to be higher, and there is a tendency that the peculiar structure of the fumed silica is lost and the fumed silica cannot be stably produced. When the BET specific surface area of ​​the hydrophilic fumed silica is too large, there is a tendency that the fumed silica cannot be stably produced.

[0083] In the masterbatch, the amount of the hydrophilic fumed silica blended is 13 parts by mass or more and 130 parts by mass or less relative to 100 parts by mass of the rubber component. That is, the masterbatch of the present embodiment can contain a high concentration of the hydrophilic fumed silica that is difficult to knead and disperse in the rubber component. Therefore, by using the masterbatch to manufacture a tire rubber composition, a tire rubber material having excellent wear resistance can be easily obtained.

[0084] In the masterbatch, the amount of the hydrophilic fumed silica blended is more preferably 15 parts by mass or more, and more preferably 20 parts by mass or more, relative to 100 parts by mass of the rubber component. On the other hand, the amount of the hydrophilic fumed silica blended is more preferably 110 parts by mass or less, and more preferably 100 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0085] When the amount of hydrophilic fumed silica is too small, the wear resistance of the obtained tire rubber material tends to be insufficient. When the amount of hydrophilic fumed silica is too large, the hydrophilic fumed silica is not sufficiently dispersed in the rubber component and a good kneaded product tends to not be obtained.

[0086] (1.3. Silane coupling agent)

[0087] By including a silane coupling agent in the masterbatch, a crosslinked structure between the hydrophobic rubber component and the hydrophilic fumed silica can be easily formed via the silane coupling agent. As a result, the dispersibility of the hydrophilic fumed silica in the masterbatch can be improved, thereby improving the wear resistance of the tire rubber material.

[0088] As a silane coupling agent, there is no particular limitation as long as it is a silane coupling agent commonly used in a rubber composition. In the present embodiment, a sulfur-containing silane coupling agent is preferred. As a sulfur-containing silane coupling agent, for example, bis(3-triethoxysilylpropyl)tetrasulfide, bis(3-triethoxysilylpropyl)disulfide, 3-trimethoxysilylpropylbenzothiazoletetrasulfide, γ-mercaptopropyltriethoxysilane, 3-octanoylthiopropyltriethoxysilane, mercaptothiocarboxylate oligomers, etc. are exemplified.

[0089] In the present embodiment, from the viewpoint of heat resistance (heat aging resistance) of the rubber composition for a tire, the silane coupling agent is preferably a block mercaptosilane, and particularly preferably a mercaptothiocarboxylate oligomer.

[0090] The mercaptothiocarboxylate oligomer is an oligomer of a thiocarboxylate having a mercapto group. Examples of the molecular structure of the mercaptothiocarboxylate oligomer are shown below. In the following molecular structure, the sum (x+y) of the number of repetitions (x) of the bonding unit A and the number of repetitions (y) of the bonding unit B is preferably in the range of 3 to 300. When within this range, the -C7H 15 The mercaptosilane covering the bonding unit B can suppress the scorch time from being shortened and can ensure good reactivity with the hydrophilic fumed silica and the rubber component. Specific examples of the mercaptothiocarboxylate oligomer include "NXT-Z45" manufactured by Momentive.

[0091]

[0092] In the masterbatch, the amount of the silane coupling agent is 1 part by mass or more and 40 parts by mass or less relative to 100 parts by mass of the rubber component. When the amount of the silane coupling agent is too small, the dispersibility of the hydrophilic fumed silica in the tire rubber composition tends to be insufficient. When the amount of the silane coupling agent is too large, the silane coupling agents tend to condense with each other, and the wear resistance of the obtained tire rubber material tends to be insufficient.

[0093] In the masterbatch, the amount of the silane coupling agent is more preferably 1.5 parts by mass or more, and more preferably 2 parts by mass or more, relative to 100 parts by mass of the rubber component. On the other hand, the amount of the silane coupling agent is more preferably 30 parts by mass or less, and more preferably 20 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0094] In addition, within the range of the amount of the silane coupling agent to be added to 100 parts by mass of the rubber component, it is preferred that the amount of the silane coupling agent be increased as the BET specific surface area of ​​the hydrophilic fumed silica increases. This is because sufficient reaction points with the hydrophilic fumed silica can be ensured. Specifically, it is particularly preferred that the amount of the silane coupling agent be increased to 0.33 mg / m2 relative to the specific surface area of ​​the added silica. 2 ~1 mg / m 2 Silane coupling agent is added within the range of

[0095] By adjusting the blending amounts of the rubber component, the hydrophilic fumed silica, and the silane coupling agent in the masterbatch to more appropriate ranges, a rubber material for a tire that can achieve good wear resistance and good fuel efficiency can be easily obtained.

[0096] (1.4. Other ingredients)

[0097] In this embodiment, in addition to the above-mentioned components (rubber component, hydrophilic fumed silica and silane coupling agent), the masterbatch also includes components to be mixed into the rubber composition. As such a component, for example, a lubricant is exemplified. By including a lubricant in the masterbatch, the kneading property of the masterbatch is improved.

[0098] Examples of lubricants include stearic acid and process oil. Lubricants may be used alone or in combination of two or more. Process oils include aromatic oils, paraffin oils, naphthenic oils, etc. These may be used alone or in combination of two or more.

[0099] The amount of the lubricant is not limited within the range that the effect of the present invention can be obtained. For example, the amount of the lubricant is preferably 1 part by mass or more and 40 parts by mass or less relative to 100 parts by mass of the rubber component. Moreover, the amount of the lubricant is more preferably 2 parts by mass or more, and more preferably 3 parts by mass or more relative to 100 parts by mass of the rubber component. On the other hand, the amount of the lubricant is more preferably 35 parts by mass or less, and more preferably 30 parts by mass or less relative to 100 parts by mass of the rubber component.

[0100] When the amount of lubricant added is too small, the kneading property of the masterbatch is poor, and the wear resistance of the obtained tire rubber material may not be sufficiently improved. When the amount of stearic acid added is too large, shearing may not be performed during kneading, and the hydrophilic fumed silica may not be fully dispersed in the rubber component.

[0101] Furthermore, the masterbatch may contain reinforcing fillers other than hydrophilic fumed silica. Examples of reinforcing fillers include carbon black, wet silica, clay, mica, talc, calcium carbonate, aluminum hydroxide, aluminum oxide, titanium oxide, and the like. When reinforcing fillers are added, a filler coupling agent may be added in an appropriate amount. The amount of reinforcing fillers added is not limited within the range in which the effects of the present invention can be obtained, and may be set to a general amount.

[0102] Furthermore, the masterbatch may contain various additives such as zinc oxide, an anti-aging agent, a plasticizer, a processing aid, a liquid polymer, a thermosetting resin, etc. The amount of these additives is not limited within the range in which the effects of the present invention can be obtained, and may be a general amount.

[0103] (2. Method for producing masterbatch)

[0104] like Figure 1 As shown, the masterbatch of the present embodiment is obtained by kneading the above-mentioned rubber component, the above-mentioned hydrophilic fumed silica, the above-mentioned silane coupling agent, and other components as necessary.

[0105] (2.1. Kneading machine)

[0106] In the present embodiment, kneading is performed using a kneader in order to sufficiently knead the hydrophilic fumed silica into the rubber component and sufficiently disperse the hydrophilic fumed silica in the masterbatch.

[0107] In the past, a Banbury mixer was used to knead silica as a filler into a rubber component and to fully disperse silica in a masterbatch or a rubber composition. The Banbury mixer presses the blended raw materials according to a pressing piece (Weight) while rotating the rotor at a high speed, thereby applying a high shear force to the raw materials and mixing the raw materials. For example, a Banbury mixer is useful in the case of kneading wet silica with a large tap density.

[0108] However, compared with wet silica, when a hydrophilic fumed silica having a low tap density and a large volume is kneaded into a rubber component using a Banbury mixer, the hydrophilic fumed silica tends to scatter. Therefore, there is a problem that the amount of hydrophilic fumed silica actually kneaded is less than the target blending amount. In addition, there is a problem that the kneaded hydrophilic fumed silica tends to aggregate in a masterbatch or a rubber composition and is not fully dispersed.

[0109] Therefore, the present inventors kneaded the hydrophilic fumed silica into the rubber component using a kneader, thereby obtaining a masterbatch in which the kneaded hydrophilic fumed silica was sufficiently dispersed while suppressing the scattering of the hydrophilic fumed silica during kneading.

[0110] Like the Banbury mixer, the kneader is a type of closed mixer. The difference from the Banbury mixer is the rotor speed. From the perspective of improving productivity, the rotor speed of the Banbury mixer is usually 45 rpm to 80 rpm, while the rotor speed of the kneader is 20 rpm to 40 rpm.

[0111] It is considered that the rotor rotation speed is lower than that of the Banbury mixer, and therefore, the bulky hydrophilic fumed silica is less likely to scatter during kneading by the kneader and is sufficiently kneaded and dispersed.

[0112] It should be noted that the present inventors have confirmed that even if the rotor speed of the Banbury mixer is set to the same level as the rotor speed of the kneader for kneading, the hydrophilic fumed silica cannot be fully kneaded in. This is believed to be because a rotor speed suitable for kneading by the Banbury mixer is set in the Banbury mixer, and the rotor structure of the Banbury mixer is optimized so that kneading is fully performed within the range of the set rotor speed.

[0113] The kneading machine may be a pressurized kneading machine or an open kneading machine without pressurization. In the present embodiment, in order to fully knead the hydrophilic fumed silica and disperse it, a pressurized kneading machine is preferred. In addition, a pressurized kneading machine capable of staged pressurization control is more preferred.

[0114] (2.2. Mixing process)

[0115] In the kneading process, the rubber component, the hydrophilic fumed silica, the silane coupling agent and other components as needed are put into a kneader for kneading. The rotor speed is 20 rpm to 40 rpm as described above. In addition, it is preferred to adjust the cooling water amount in such a way that the temperature of the kneaded product is within the range of 130° C. to 160° C. In addition, in the case of a pressurized kneader, the kneading time is preferably about 20 minutes to 60 minutes. The kneading time of an open kneader is preferably longer than that of a pressurized kneader. After the kneading is completed, a masterbatch kneaded with the above-mentioned components is obtained. The masterbatch is a masterbatch containing a large volume of hydrophilic fumed silica, which is usually difficult to fully knead and disperse, at a high concentration.

[0116] (3. Rubber composition for tire)

[0117] The tire rubber composition of the present embodiment comprises at least one (rubber component) selected from the group consisting of natural rubber and synthetic rubber, hydrophilic fumed silica and a silane coupling agent. The natural rubber and synthetic rubber may be the above-mentioned natural rubber and synthetic rubber. The same is true for the hydrophilic fumed silica and the silane coupling agent.

[0118] From the perspective of improving wear resistance, the content of NR in the total rubber component is preferably 30 parts by mass or more, and more preferably 40 parts by mass or more. In addition, from the perspective of achieving a balance in tire characteristics that is a feature of the present invention, the content of NR is preferably 80 parts by mass or less, and more preferably 75 parts by mass or less.

[0119] For the reason of excellent processability during extrusion, the content in the total rubber component when including SBR is preferably more than 10 parts by mass, more preferably more than 20 parts by mass. In addition, for the reason of being able to suppress the heat generation inside the tire, the content of SBR is preferably less than 50 parts by mass, more preferably less than 40 parts by mass.

[0120] For the reason of improving wear resistance, the content of BR in the total rubber component when BR is included is preferably 20 parts by mass or more, and more preferably 30 parts by mass or more. In addition, for the reason of suppressing heat generation inside the tire, the content of BR is preferably 50 parts by mass or less, and more preferably 40 parts by mass or less.

[0121] In the tire rubber composition, the amount of the hydrophilic fumed silica is 5 parts by mass or more and 90 parts by mass or less relative to 100 parts by mass of the rubber component. When the amount of the hydrophilic fumed silica is too small, there is a tendency that the wear resistance of the obtained tire rubber material cannot be fully obtained. When the amount of the hydrophilic fumed silica is too large, there is a tendency that the hydrophilic fumed silica is not fully dispersed in the rubber component and a good kneaded product cannot be obtained.

[0122] In the tire rubber composition, the amount of the hydrophilic fumed silica is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, relative to 100 parts by mass of the rubber component. On the other hand, the amount of the hydrophilic fumed silica is preferably 70 parts by mass or less, more preferably 55 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0123] Furthermore, the range of the BET specific surface area of ​​the hydrophilic fumed silica is preferably the same as the range of the BET specific surface area of ​​the hydrophilic fumed silica contained in the above-mentioned masterbatch.

[0124] In the tire rubber composition, the amount of the silane coupling agent is 1.5 parts by mass or more and 30 parts by mass or less relative to 100 parts by mass of the above-mentioned rubber component. When the amount of the silane coupling agent is too small, there is a tendency that the dispersibility of the silicon dioxide compound such as the hydrophilic fumed silica in the tire rubber composition is insufficient. When the amount of the silane coupling agent is too large, the silane coupling agents are easily condensed with each other, and the wear resistance of the obtained tire rubber material may not be fully improved.

[0125] In the tire rubber composition, the amount of the silane coupling agent is preferably 2.0 parts by mass or more, more preferably 2.5 parts by mass or more, relative to 100 parts by mass of the rubber component. On the other hand, the amount of the silane coupling agent is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0126] In the tire rubber composition, by adjusting the blending amounts of the rubber component, hydrophilic fumed silica, and silane coupling agent to more appropriate ranges, a tire rubber material that can achieve good wear resistance and good fuel efficiency can be easily obtained.

[0127] The tire rubber composition of the present embodiment preferably includes the above-mentioned masterbatch. That is, the tire rubber composition of the present embodiment is preferably manufactured using the above-mentioned masterbatch. By using the above-mentioned masterbatch, a tire rubber composition containing a predetermined amount of hydrophilic fumed silica that is difficult to knead and difficult to disperse can be easily obtained.

[0128] In the present embodiment, the rubber composition for a tire may further contain components compounded in a rubber composition in addition to the above-mentioned components (the above-mentioned rubber component, the hydrophilic fumed silica, and the silane coupling agent).

[0129] In the present embodiment, the tire rubber composition preferably includes wet silica. Wet silica is generally a silica synthesized by a neutralization reaction of sodium silicate and an inorganic acid (usually sulfuric acid). Wet silica is roughly divided into precipitated silica and gel-based silica. In the present embodiment, wet silica is preferably precipitated silica.

[0130] However, for wet silica, the amount of water adsorbed on the surface of the silanol group is more than that of fumed silica. It is believed that the adsorbed water hinders the formation of a cross-linked structure. Therefore, the amount of wet silica required for the effect caused by the cross-linked structure via the silanol group is more than that of fumed silica. In other words, in the case of wanting to obtain an effect of the same degree as that of fumed silica, the amount of wet silica is more than that of fumed silica.

[0131] Furthermore, since wet silica has a smaller BET specific surface area than fumed silica, there is a tendency for a larger blending amount required to achieve a target hardness of a tire rubber material.

[0132] As described above, from the viewpoint of the properties of the tire rubber material, the blending amount of wet silica is preferably small. On the other hand, fumed silica is more expensive than wet silica, so from the viewpoint of cost, wet silica is preferably contained.

[0133] When the tire rubber composition includes wet silica, the amount of wet silica is preferably greater than 0 mass parts and less than 90 mass parts, more preferably greater than 0 mass parts and less than 70 mass parts, relative to 100 mass parts of the rubber component. When the amount of wet silica is too much, there is a tendency that the wet silica is not fully dispersed in the rubber component and a good kneaded product cannot be obtained.

[0134] In this embodiment, the BET specific surface area of ​​wet silica is preferably 40 m 2 / g or more, 70m 2 / g or more, 110m 2 / g or more. By making the BET specific surface area 40m 2 / g or more, there is a tendency that sufficient wet grip can be obtained. In addition, the BET specific surface area of ​​wet silica is preferably 220 m 2 / g or less, 200m 2 / g or less. By making the BET specific surface area 220m 2 / g or less, there is a tendency that good dispersibility can be obtained.

[0135] The wet silica may be mixed with the fumed silica before the step of kneading with the rubber component, or may be added in the step of kneading the fumed silica and the rubber component.

[0136] In addition, the tire rubber composition may contain processing oil. As processing oil, for example, aromatic oil, paraffin oil, naphthenic oil, etc. can be exemplified. These can be used alone or in combination of two or more. The amount of processing oil is preferably 2 to 10 parts by mass, more preferably 4 to 8 parts by mass, relative to 100 parts by mass of the rubber component.

[0137] The tire rubber composition may contain reinforcing fillers other than hydrophilic fumed silica and wet silica. Examples of reinforcing fillers include carbon black, clay, mica, talc, calcium carbonate, aluminum hydroxide, aluminum oxide, titanium oxide, etc. In addition, when reinforcing fillers are added, a filler coupling agent may be added in an appropriate amount. The amount of these reinforcing fillers added may be set to a general amount within the range in which the effects of the present invention can be obtained.

[0138] When carbon black is contained as the reinforcing filler, the amount of carbon black blended is preferably greater than 0 parts by mass and 60 parts by mass or less relative to 100 parts by mass of the rubber component.

[0139] The tire rubber composition may include various tire components such as a vulcanizing agent or a crosslinking agent, a vulcanization accelerator, sulfur, zinc oxide, stearic acid, an anti-aging agent, a plasticizer, a processing aid, a liquid polymer, a thermosetting resin, etc. Such components may be mixed before or after the tire rubber composition is kneaded to help the vulcanization or crosslinking of the tire rubber composition. The amount of these tire components may be set to a general amount within the range in which the effect of the present invention can be obtained. For example, the total amount of sulfur and the vulcanization accelerator is preferably 1.5 parts by mass or more and 7 parts by mass or less relative to 100 parts by mass of the above-mentioned rubber component.

[0140] The rubber composition for a tire of the present embodiment has an excellent balance among wear resistance, fuel economy, and wet grip performance, and is therefore suitable for passenger car tires such as all-season tires or tire treads thereof.

[0141] (4. Method for producing tire rubber composition)

[0142] like Figure 2As shown, the tire rubber composition is preferably obtained by mixing the above-mentioned masterbatch, the above-mentioned rubber component and the above-mentioned components as required. That is, in the present embodiment, the tire rubber composition is preferably manufactured by mixing other components into the masterbatch. In addition, in addition to the rubber component contained in the masterbatch, the rubber component is also mixed. On the other hand, hydrophilic fumed silica may be further mixed or not mixed.

[0143] In the manufacture method of the above-mentioned masterbatch, a kneading machine is used for mixing, but the mixing machine used in the mixing of the rubber composition for tire is not particularly limited. That is, a Banbury mixer can be used, and a kneading machine can also be used. The masterbatch fully kneaded and fully dispersed using hydrophilic fumed silica is mixed, so even if a Banbury mixer is used for mixing, a mixed product (rubber composition for tire) can be obtained while maintaining a good dispersion state of the hydrophilic fumed silica. A kneading machine can be used for mixing, but from the viewpoint of productivity improvement, a Banbury mixer is preferably used for mixing.

[0144] The kneading conditions may be such that the masterbatch and the respective components are sufficiently kneaded.

[0145] In addition, the tire rubber composition can also be manufactured without using a masterbatch. In this case, as described above, the hydrophilic fumed silica is large in volume, so a kneader is used to manufacture the tire rubber composition. The tire rubber composition can be manufactured by simultaneously putting all the components into a kneader and mixing them, or by putting each component in stages to manufacture the tire rubber composition.

[0146] (5. Rubber materials for tires)

[0147] The tire rubber material of the present embodiment is a material obtained by vulcanizing the tire rubber composition. Therefore, the components and their blending amounts contained in the tire rubber material are the same as the types and blending amounts of the components (rubber component, hydrophilic fumed silica, silane coupling agent, etc.) contained in the above-mentioned tire rubber composition.

[0148] Common tire rubber materials containing only carbon black or wet silica as a filler include a structure in which rubber and carbon black or silica are cross-linked via sulfur, a structure in which rubber and carbon black or silica are cross-linked via a silane coupling agent, and the like.

[0149] On the other hand, the tire rubber material of the present embodiment contains hydrophilic fumed silica derived from the above-mentioned tire rubber composition. It is considered that the tire rubber material contains: a structure formed by crosslinking the rubber component and the hydrophilic fumed silica via sulfur; a structure formed by crosslinking the rubber component and the hydrophilic fumed silica via a silane coupling agent; and a structure caused by the hydrophilic fumed silica.

[0150] It is considered that this structure breaks or connects when stress is applied to the tire rubber material, and as a result, it is considered that the stress is dispersed and the wear resistance of the tire rubber material is improved.

[0151] It should be noted that the present inventors have confirmed that the above-mentioned effect is reduced in the case of hydrophobic fumed silica.

[0152] In the present embodiment, at 23° C., M100 (stress at 100% elongation: MPa), TB (tensile breaking strength: MPa), and EB (tensile breaking elongation: %) of the rubber material for a tire satisfy the following relationship.

[0153] 4000(MPa·% / MPa)≤TB×EB / M100≤13000(MPa·% / MPa).

[0154] That is, the TB and EB of the rubber material for tires of the present embodiment are relatively high, and M100 is relatively low. In the past, the wear resistance of rubber materials for tires was evaluated by M300 (stress at 300% elongation). However, the wear resistance of tires mounted on cars for running is mostly unrelated to M300, and the present inventors have found that M300 is not suitable for evaluating the wear resistance of rubber materials for tires. The present inventors have studied the stress-strain curve (SS curve) of rubber materials for tires, and focused on the elongation when the curve rises, and the following insights were obtained: As shown below, rubber materials with low M100 show excellent wear resistance.

[0155] That is, it is believed that: in the case of the uneven dispersion of the filler in the rubber material for tire, in the case of the uneven strength caused by the density of crosslinking, such an uneven structure can become the starting point of the destruction of the rubber material, and abrasion aggravates. The uniform performance of the filler is measured by the stress (M100) during the rise of the stress-strain curve in the tensile test of the rubber material for tire. This is because the more uneven the dispersion of the filler, the easier it is to apply force to the uneven structure of the rubber material, and there is a tendency for M100 to become higher. On the other hand, in the case of the uniform dispersion of the filler, the structure that becomes the starting point of stress is sparse, so it is not easy to apply stress, and there is a tendency for M100 to become lower.

[0156] Therefore, by uniformly dispersing (finely dispersing) the filler, especially the hydrophilic fumed silica which is not easily dispersed, the M100 of the rubber material becomes lower and the wear resistance is improved. In addition, the filler is uniformly dispersed, so that the structure that becomes the starting point of destruction in the rubber material is reduced, the breaking strength (TB) and the breaking elongation (EB) are improved, and the wear resistance is improved.

[0157] Furthermore, by setting TB×EB / M100 (MPa·% / MPa) within the above range, the fuel efficiency and wet grip performance of the rubber material for a tire are also favorably affected.

[0158] In the present embodiment, TB×EB / M100 is more preferably 4400 MPa·% / MPa or more and 11000 MPa·% / MPa or less, and further preferably 5600 MPa·% / MPa or more and 9000 MPa·% / MPa or less.

[0159] Furthermore, M100 is preferably 1.5 MPa to 5.5 MPa, more preferably 1.7 MPa to 5.0 MPa, and even more preferably 1.9 MPa to 4.5 MPa. When M100 is within the above range, the wear resistance of the rubber material for a tire is improved.

[0160] It should be noted that M100, TB and EB can be measured in accordance with JIS K 6251. The detailed measurement method is described in the examples.

[0161] In addition, the A hardness of the rubber material for a tire is preferably 55 or more and 75 or less. The A hardness of the rubber material for a tire varies depending on the purpose of the tire, but by making the A hardness of the rubber material for a tire within the above range, the rubber material for a tire can be appropriately applied to various tires. The A hardness of the rubber material for a tire is more preferably 58 or more and 73 or less, and further preferably 60 or more and 71 or less.

[0162] (6. Tires)

[0163] The tire of the present embodiment includes a tire component formed by the above-mentioned tire rubber material. As a result, the tire of the present embodiment can show a high level of balanced wear resistance, low fuel consumption performance, and wet grip performance. Therefore, the tire of the present embodiment can be appropriately applied to passenger car tires such as all-season tires. As tire components formed by the above-mentioned tire rubber material, for example, tread, base tread, sidewall, tire clincher, etc. are exemplified, and in particular, a tire component that is grounded in the tire is preferably shown.

[0164] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment at all, It can change in various aspects within the scope of this invention.

[0165] The above description has been given of the rubber composition for tires and the rubber material for tires, but the rubber composition for tires and the rubber material for tires can also be used for purposes other than tires. For example, the rubber material for tires can be used for fenders, conveyor belts, vibration-proof rubber, rubber tracks, rubber gloves, etc.

[0166] Example

[0167] Hereinafter, the present invention will be described in further detail in the examples, but the present invention is not limited to the following examples.

[0168] (Experiment 1)

[0169] (Preparation of Masterbatch)

[0170] The following components were added to a 0.5 L pressure kneading machine so that the compounding amount relative to 100 parts by mass of the rubber component was the compounding amount shown in Table 1. After the addition, the components were kneaded for about 30 minutes at a rotor speed of 20 rpm to 40 rpm and a kneaded product temperature of 130° C. to 160° C. The cylinder pressure was 0.7 MPa. After the kneading was completed, the mixture was cooled to room temperature and taken out to obtain a masterbatch.

[0171] (A) Rubber component

[0172] (A-1) Natural rubber made in Vietnam: SVR

[0173] (A-2) SBR (manufactured by Asahi Kasei Chemicals Co., Ltd., E581)

[0174] (A-3) BR (Made by JSR, BR01)

[0175] (B) Filler

[0176] (B-1) Hydrophilic fumed silica (manufactured by Tokuyama, REOLOSIL QS-30C, nitrogen adsorption BET specific surface area: 300 m 2 / g, tap density: 100g / L)

[0177] (B-2) Wet silica (manufactured by Tosoh Silica, Nipsil AQ, nitrogen adsorption BET specific surface area: 200 m 2 / g, tap density: 300g / L)

[0178] (B-3) Carbon black (manufactured by Tokai Carbon, SEAST 6, nitrogen adsorption BET specific surface area: 120 m 2 / g, tap density: 400g / L)

[0179] (C) Silane coupling agent

[0180] (C-1) Mercaptothiocarboxylate oligomer (manufactured by Momentive, NXT-Z45)

[0181] (C-2) Bis-(3-triethoxysilylpropyl) disulfide (manufactured by Evonik, Si75)

[0182] (D) Other ingredients

[0183] (D-1) Lubricant (stearic acid, NOF, beaded stearic acid YR)

[0184] (D-2) Processing oil (manufactured by Fuji Kosan, Aromax 3 (TDAE Oil))

[0185] (D-3) Anti-aging agent (Seiko Chemical, Ozonone 6C)

[0186] Table 1

[0187]

[0188] (Preparation of tire rubber composition)

[0189] The obtained masterbatch, the above-mentioned components as required, and (D-4) and (D-5) shown below are put into a closed Banbury mixer with a volume of 1.7 L. After the introduction, the mixture is kneaded for about 10 minutes in a manner such that the rotor speed is in the range of 45 rpm to 80 rpm and the temperature of the kneaded product is in the range of 130° C. to 160° C. The punch pressure during kneading is in the range of 0.5 MPa to 4.0 MPa. After the kneading is completed, the mixture is cooled to room temperature to obtain a kneaded product.

[0190] (D) Other ingredients

[0191] (D-4) Lubricant (zinc oxide, made by the same chemical method, three types of zinc oxide)

[0192] (D-5) Sulfur (produced by Tsurumi Chemical Industry, Jinhua printing oil into micronized sulfur)

[0193] The following (D-6) to (D-7) were added to the obtained kneaded product, and mixed using a 6-inch roll tester to obtain a tire rubber composition. The formulation of the obtained tire rubber composition is shown in Table 2. It should be noted that the masterbatch of Standard Manufacturing Example 1 was used for Standard Examples 1 to 5, the masterbatch of Manufacturing Example 1 was used for Examples 1 to 8, 10 and 11, and the masterbatch of Manufacturing Example 2 was used for Examples 9 and 12.

[0194] (D) Other ingredients

[0195] (D-6) Vulcanization accelerator (N-cyclohexyl-2-benzothiazole sulfenamide (abbreviation: CBS), manufactured by Sanshin Chemical Industry, SANCELER CM-G)

[0196] (D-7) Vulcanization accelerator (1,3-diphenylguanidine (abbreviation: DPG), manufactured by Sanshin Chemical Industry, SANCELER D)

[0197] Table 2

[0198]

[0199] The obtained tire rubber composition was used to prepare a test piece for the following evaluation. The following physical properties were evaluated using the obtained test piece.

[0200] (Processability: Mooney viscosity)

[0201] The Mooney viscosity (ML1+4 100°C) at 100°C of the obtained test piece of the rubber composition for tires was measured using a Mooney viscometer (VR-1132 manufactured by Ueshima Seisakusho Co., Ltd.) in accordance with JIS K6300-1. When the Mooney viscosity is low, the processability of the rubber composition for tires tends to be good. The results are shown in Table 2.

[0202] (Preparation of rubber materials for tires)

[0203] Next, the obtained tire rubber composition was press-vulcanized at 160° C. for 10 minutes to obtain a tire rubber material. Test pieces for the following evaluations were prepared from the obtained tire rubber material. The following physical properties were evaluated using the obtained test pieces.

[0204] (A Hardness)

[0205] The hardness (Shore A hardness) of the obtained test piece of the tire rubber material was measured using a durometer in accordance with JIS K6253 Type A. The target A hardness of the tire rubber material varies depending on the purpose of the tire, but in this embodiment, the A hardness of the test piece was changed in the standard example and the embodiment to adjust the hardness to the same degree. The results are shown in Table 2.

[0206] (M100)

[0207] The obtained test piece was processed into a No. 3 dumbbell test piece and subjected to a tensile test at a tensile speed of 500 mm / min in accordance with JIS K6251. In the tensile test, the stress (M100: MPa) at 100% elongation at 23°C±2°C was measured.

[0208] (Fracture characteristics)

[0209] The obtained test piece was processed into a No. 3 dumbbell test piece and subjected to a tensile test at a tensile speed of 500 mm / min in accordance with JIS K6251. In the tensile test, the tensile breaking strength (TB: MPa) and the tensile breaking elongation (EB: %) at 23°C ± 2°C were measured.

[0210] TB×EB / M100 (MPa·% / MPa) was calculated from the measured values ​​of M100, TB, and EB obtained above. The results are shown in Table 2.

[0211] (Low fuel consumption performance: tanδ at 60℃)

[0212] The obtained test piece of the tire rubber material was measured under the following conditions using a dynamic viscoelasticity tester (VR-7130 manufactured by Ueshima Seisakusho Co., Ltd.) in accordance with JIS K6394. Tan δ (60° C.) was calculated from the measured value at 60° C.

[0213] Measurement temperature: 60℃.

[0214] Static strain: 10%.

[0215] Dynamic strain: ±2%.

[0216] Frequency: 10Hz.

[0217] The calculated tanδ(60℃) of standard examples 1 to 5 is set to 1.0, and the rolling resistance index is calculated according to the following calculation formula for the examples with the same A hardness. For example, the tanδ(60℃) of standard example 3 is set to 1.0, and the rolling resistance index of examples 4 to 6 is calculated. The larger the index, the better the rolling resistance. The results are shown in Table 2.

[0218] (Rolling resistance index) = (tan δ (60°C) of standard example) / (tan δ (60°C) of example).

[0219] (Abrasion resistance: FPS abrasion loss)

[0220] For the test piece of the obtained tire rubber material, the FPS wear tester (AB-2012 manufactured by Ueshima Manufacturing Co., Ltd.) was used to measure the FPS wear amount under the conditions of temperature of 20°C, load of 20N and 40N, slip rate of 10%, and test time of 2 minutes. The volume loss was calculated based on the FPS wear amount, and the loss amount of standard examples 1 to 5 was set to 1.0. For the examples with the same A hardness, the wear index was calculated according to the following calculation formula. The larger the index, the better the wear resistance. The results are shown in Table 2.

[0221] (Abrasion index) = (loss amount of standard example) / (loss amount of example).

[0222] (Wet grip performance: tanδ at 0°C)

[0223] The obtained test piece of the tire rubber material was measured in accordance with JIS K6394 using a dynamic viscoelasticity tester (VR-7130 manufactured by Ueshima Seisakusho Co., Ltd.) under the following conditions. tan δ (0° C.) was calculated from the measured value at 0° C.

[0224] Measurement temperature: 0℃.

[0225] Static strain: 10%.

[0226] Dynamic strain: ±2%.

[0227] Frequency: 10Hz.

[0228] The calculated tanδ (0°C) of Standard Examples 1 to 5 was set as 1.0, and the wet grip index was calculated for Examples having the same A hardness according to the following calculation formula. The larger the index, the better the wet grip. The results are shown in Table 2.

[0229] (Wet grip index) = (tan δ (0°C) of Example) / (tan δ (0°C) of Standard Example).

[0230] (Tire wear resistance)

[0231] The tire was trial-produced by attaching the tread of the obtained tire rubber composition to the base tire and performing a tire retreading method of vulcanization bonding. The size of the tire is 11R22.5. The trial-produced tire is attached to the towing part of the trailer of the truck, and a wear test is performed. According to the wear volume at the time point of 10,000 kilometers of travel, the wear volume of each standard example is set to 1.0, and the wear index is calculated according to the following calculation formula for the embodiment with the same A hardness. The larger the index, the better the wear resistance. The results are shown in Table 2.

[0232] (Abrasion index) = (Abrasion volume of standard example) / (Abrasion volume of example).

[0233] It can be confirmed from Table 2 that the tire rubber material containing hydrophilic fumed silica and in which M100, TB and EB satisfy the above relationship has a better balance among wear resistance, fuel economy and wet grip than the tire rubber material not containing hydrophilic fumed silica or in which M100, TB and EB do not satisfy the above relationship.

[0234] Furthermore, it was confirmed that the wear property of a tire using a tire material containing hydrophilic fumed silica and in which M100, TB, and EB satisfy the above relationship as the tread is superior to the wear property of a tire using a tire material not containing hydrophilic fumed silica or in which M100, TB, and EB do not satisfy the above relationship as the tread.

Claims

1. A masterbatch, wherein: The present invention contains 13 to 130 parts by mass of hydrophilic fumed silica and 1 to 40 parts by mass of a silane coupling agent per 100 parts by mass of a rubber component which is at least one selected from the group consisting of natural rubber and synthetic rubber.

2. The masterbatch according to claim 1, wherein The BET specific surface area of ​​the hydrophilic fumed silica is 50 m 2 / g and above and 500m 2 / g or less.

3. The masterbatch according to claim 1 or 2, wherein: The lubricant is contained in an amount of 1 part by mass or more and 40 parts by mass or less based on 100 parts by mass of the rubber component.

4. A method for producing a masterbatch, wherein: have: This is a process of kneading the rubber component, hydrophilic fumed silica, and silane coupling agent using a kneader.

5. The method for producing a masterbatch according to claim 4, wherein: The BET specific surface area of ​​the hydrophilic fumed silica is 50 m 2 / g and above and 500m 2 / g or less.

6. The method for producing a masterbatch according to claim 4 or 5, wherein: Lubricants are also mixed.

7. A rubber composition for a tire, wherein: The present invention contains 5 to 90 parts by mass of hydrophilic fumed silica and 1.5 to 30 parts by mass of a silane coupling agent, based on 100 parts by mass of the total rubber component composed of at least one selected from the group consisting of natural rubber and synthetic rubber.

8. The tire rubber composition according to claim 7, wherein The rubber composition for a tire contains more than 0 parts by mass and 90 parts by mass or less of wet silica relative to 100 parts by mass of the total rubber components.

9. The tire rubber composition according to claim 7 or 8, wherein The BET specific surface area of ​​the hydrophilic fumed silica is 50 m 2 / g and above and 500m 2 / g or less.

10. The rubber composition for a tire according to claim 8, wherein The BET specific surface area of ​​the wet silica is 40 m 2 / g and above 220m 2 / g or less.

11. The rubber composition for a tire according to claim 7, wherein Include: The masterbatch according to claim 1 or 2.

12. A method for producing a rubber composition for a tire, wherein: have: A step of kneading the masterbatch according to claim 1 or 2 and at least one selected from the group consisting of natural rubber and synthetic rubber.

13. A rubber material for a tire, wherein: The present invention comprises 5 parts by mass or more and 90 parts by mass or less of hydrophilic fumed silica and 1.5 parts by mass or more and 30 parts by mass or less of a silane coupling agent, based on 100 parts by mass of the total rubber component composed of at least one selected from the group consisting of natural rubber and synthetic rubber, The stress M100, tensile strength at break TB and tensile elongation at break EB of the tire rubber material at 100% elongation satisfy the following relationship, wherein the unit of the stress M100 at 100% elongation is MPa, the unit of the tensile strength at break TB is MPa, and the unit of the tensile elongation at break EB is %. 4000≤TB×EB / M100≤13000.

14. The rubber material for a tire according to claim 13, wherein The tire rubber material contains more than 0 parts by mass and 90 parts by mass or less of wet silica based on 100 parts by mass of the total rubber component.

15. The rubber material for a tire according to claim 13 or 14, wherein The BET specific surface area of ​​the hydrophilic fumed silica is 50 m 2 / g and above and 500m 2 / g or less.

16. The rubber material for a tire according to claim 14, wherein The BET specific surface area of ​​the wet silica is 40 m 2 / g and above 220m 2 / g or less.

17. A tire, wherein: Include: A tire component formed from the tire rubber material according to claim 13 or 14.

Citation Information

Patent Citations

  • Manufacturing method of rubber composition, rubber composition and pneumatic tire

    JP2005213353A

  • Rubber composition for tire tread

    JP2012158661A

  • Rubber composition for tire, and pneumatic tire

    JP2018150420A

  • Vulcanized rubber composition and pneumatic tire

    WO2018128141A1